(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
Named data networking is one assuring instantiation of information concentric network ing where emphasis is placed on content information of some vulnerable extent to some form of denial of service attacks. This problem is more severe especially during content transmission with minimum signaling and overhead costs on the global Internet. We adopted the use of an efficient protocol known as the listen first broadcast later for inter est content as they are transmitted by the consumer in search for data between nodes of producer and rendezvous in motion. This framework can offer numerous advantages to real-time applications like video and audio using in-network caching and direct content forwarding. Simulation results in ndnSIM 2.1 and Wireshark present successful simple mentation of the producer to rendezvous scalable content delivery between the links. This scheme ensures preventing attackers at both ends of the links without affecting non- attacking consumers and producers.